Analisis Strategi Pemasaran untuk Meningkatkan Jumlah Iklan (Studi Kasus pada Radio Kanjuruhan FM) - Ike Ratnasari; Anggraini Wijayanti (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2019)
The large amount of competition makes radio stations provide innovation as a form of marketing strategy to attract listeners and advertisers. In order to maintain the viability of its business, an effective marketing strategy is needed. One effort to find out the right marketing strategy for the company is to use a SWOT analysis. The purpose of this research is to find out the marketing strategies used and what should have been used Radio Kanjuruhan FM so far in increasing the number of advertisements. The marketing strategy carried out by Radio Kanjuruhan FM is a marketing mix that includes 4 components, namely, product, price, place, promotion. These 4 components provide an important role in supporting the progress of Radio Kanjuruhan FM. Based on the SWOT Radio Analysis Kanjuruhan FM can increase promotions, collaborate with local radio, increase the number of employees, utilize technology, and provide competitive prices. Whereas from the marketing strategy which includes, market segmentation, setting the target market (market targeting) and positioning (positioning) of Kanjuruhan FM Radio can find out which market segments have been listening to Radio Kanjuruhan FM.